A novel friction-actuated 2-DOF high precision positioning stage with hybrid decoupling structure. (January 2022) - Tian, Yanling; Huo, Zhichen; Wang, Fujun; Liang, Cunman; Shi, Beichao; Zhang, Dawei
Highlights: A novel friction-actuated 2-DOF positioner with hybrid decoupling structure. A coarse-fine cooperatively actuation principle is developed. The decoupling control strategy is adopted to reduce coupling error. The proposed positioner can realize large stroke positioning with high precision. Abstract: This paper proposes a novel friction-actuated two degree-of-freedom positioning stage with large motion stroke, high resolution and low coupling rate. A parallelly decoupled driving unit and the serially configured sliders are utilized together to realize hybrid output decoupling, and a clamping unit is adopted to adjust the friction force between friction piece and moving platform, which can improve the output characteristic while reduce the amount of PZT stacks. In addition, the coarse-fine cooperatively actuation principle is developed to realize large stroke positioning with high accuracy, and the decoupling control strategy is adopted to reduce the accumulated coupling error. The analytical modeling is conducted to explore the step displacement of driving unit, and a prototype is fabricated to investigate the performance of the positioning stage. The experimental results show that the step displacements in X and Y axes are 11.3 μm and 10.6 μm, and the cross-coupling rates after decoupling compensation are 0.07% and 0.14%, respectively. The maximum output velocity and horizontal loading capacity is 1.54 mm/s and 1.2 N, respectively, and the resolution is tested as 20 nm.